2022
DOI: 10.3390/foods11050683
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Effect of Refining on the Oil Extracted from Durum Wheat By-Products

Abstract: Durum wheat is one of the most important cereal grains worldwide, used mostly for pasta making and bakery products. The by-products derived for the milling process, although very abundant, have only limited use. The aim of this work was to characterize the oils extracted from the by-products of debranning (DP) and milling processes (MP) of durum wheat and to follow the changes due to the refining process on the minor components. The results showed that DP had significantly higher oil content than MP, but it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Durum wheat oil, prepared as reported in Squeo et al [ 25 ], was provided by Casillo Next Food Srl (Corato, Italy). Wheat flour type 0 (Casillo Spa, Corato, Italy) (carbohydrate 72 g/100 g; proteins 11 g/100 g; fat 2 g/100 g; fiber 2 g/100 g); sunflower oil (Olearia De Santis, Bitonto, Italy); olive oil (Olearia De Santis, Bitonto, Italy); yeast ( Saccharomyces cerevisiae, Mulino Caputo, Naples, Italy); and sea salt (Atisale Spa, Margherita di Savoia, Italy) were purchased from local retailers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Durum wheat oil, prepared as reported in Squeo et al [ 25 ], was provided by Casillo Next Food Srl (Corato, Italy). Wheat flour type 0 (Casillo Spa, Corato, Italy) (carbohydrate 72 g/100 g; proteins 11 g/100 g; fat 2 g/100 g; fiber 2 g/100 g); sunflower oil (Olearia De Santis, Bitonto, Italy); olive oil (Olearia De Santis, Bitonto, Italy); yeast ( Saccharomyces cerevisiae, Mulino Caputo, Naples, Italy); and sea salt (Atisale Spa, Margherita di Savoia, Italy) were purchased from local retailers.…”
Section: Methodsmentioning
confidence: 99%
“…The fatty acid composition of the oils used in the focaccia preparation was analyzed as described by Squeo et al [ 25 ]. A gas chromatograph (mod.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study showed that, despite the differences found between the samples throughout 3 weeks of refrigerated storage, buttermilk may be effectively used to produce quark cheese with suitable technological properties and good sensory features. Squeo et al [ 9 ] characterized the oils extracted from durum wheat debranning (DP) and milling (MP) by-products, to be proposed as edible oils after refining. An oil content of around 6 and 5% was found for DP and MP, respectively, both being composed of around 62% of polyunsaturated fatty acids and a rich profile of different phytochemicals.…”
mentioning
confidence: 99%